Impaired Inhibition by Avibactam and Resistance to the Ceftazidime-Avibactam Combination Due to the D(179)Y Substitution in the KPC-2 β-Lactamase - Compain, Fabrice (Antimicrob Agents Chemother, 2017)
The ceftazidime-avibactam antibiotic combination was recently shown to be at risk for the emergence of resistance under treatment. To gain insight into the underlying mechanism, we have analyzed the catalytic properties of a Klebsiella pneumoniae carbapenemase type 2 (KPC-2) β-lactamase harboring the D(179)Y substitution. We show that impaired inhibition by avibactam combined with significant residual activity for ceftazidime hydrolysis accounts for the resistance. In contrast, the D(179)Y substitution abolished the hydrolysis of aztreonam and imipenem, indicating that these drugs might provide therapeutic alternatives.